The Effect of Heel Raise and Sit-to-Stand (STS) Exercises on the Balance of Post-Stroke Patients: A Quasi-Experimental Study - Adriyansar, Reza; Buston, Erni; Efendi, Pauzan; Husni, Husni; Sahran, Sahran (Media Publikasi Cendekia Indonesia, 2025)
Brain blood vessels block or rupture in cerebrovascular disease (CVD), limiting oxygen and nutrient delivery to brain tissue. An untreated stroke can cause lasting brain damage, disability, or even death. Common complications include muscle weakness, coordination issues, difficulty swallowing, slurred speech, reduced sensitivity, facial or bodily paralysis, and balance problems. Stroke survivors are advised to engage in physical exercises such as heel raises and sit-to-stand (STS) movements to address balance impairments. This study aimed to evaluate the effect of heel raise and STS exercises on improving balance in post-stroke patients at the Sawah Lebar Public Health Center in Bengkulu Municipality. A quasi-experimental design was employed with 52 participants split evenly into intervention and control groups. Participants were selected using purposive sampling, and balance was measured using the Berg Balance Scale (BBS). The Mann-Whitney test revealed a significant difference in balance scores between groups (p-value = 0.000, p ≤ 0.05, indicating a positive effect of the intervention). Before intervention, both groups experienced balance impairments, with the intervention group scoring 33.04 (SD 6.095) and the control group 31.54 (SD 4.933). After the intervention, scores improved more notably in the intervention group (scored by 38.04, SD 5.744) compared to the control group (scored by 32.65, SD 5.012), p-value = 0.000 (Mann-Whitney). Intervention increased the average score by +5.00 and control by +1.12. Heel raise and sit-to-stand (STS) exercises significantly improved balance in post-stroke patients and may serve as effective rehabilitation strategies, although further larger randomized controlled trials are needed to confirm these findings.